2016
DOI: 10.1002/pon.4213
|View full text |Cite|
|
Sign up to set email alerts
|

Illness representations, coping, and illness outcomes in people with cancer: a systematic review and meta-analysis

Abstract: Objective Cancer is associated with negative health and emotional outcomes in those affected by it, suggesting the need to better understand the psychosocial determinants of illness outcomes and coping. The common sense model is the leading psychological model of selfregulation in the face of illness and assumes that subjective illness representations explain how people attempt to cope with illness. This systematic review and meta-analysis examines the associations of the common sense model's illness represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
116
3
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(151 citation statements)
references
References 81 publications
22
116
3
10
Order By: Relevance
“…Our interview findings highlight several factors influencing adjustment. As previously shown for PCa and other cancer types, illness perceptions were important in adjustment, influencing positive reframing, and were often shaped by health professionals discussing the generally positive prognosis . A nurse‐led intervention to help men on WW cognitively reframe their diagnosis indicated that uncertainty can be reduced and quality of life improved, but further larger scale work is warranted.…”
Section: Discussionsupporting
confidence: 86%
“…Our interview findings highlight several factors influencing adjustment. As previously shown for PCa and other cancer types, illness perceptions were important in adjustment, influencing positive reframing, and were often shaped by health professionals discussing the generally positive prognosis . A nurse‐led intervention to help men on WW cognitively reframe their diagnosis indicated that uncertainty can be reduced and quality of life improved, but further larger scale work is warranted.…”
Section: Discussionsupporting
confidence: 86%
“…Participants in Group 2 were generally younger than those in Group 4, had an average of one additional chronic illness per person (whereas only one participant in Group 4 had an additional chronic illness), reported they received more misinformation and misdiagnoses from health professionals, described less positive social support interactions, and perceived more, and more severe, cancer-related psychosocial consequences. This is in line with previous research that suggests that cancer patients who are younger [2123], have additional chronic illnesses [24, 25], less social support [26, 27], and more negative illness representations [28], are more likely to experience higher levels of distress. This suggests that together with these potential risk factors, people who also have a history of long-term anxiety/depression and who have not developed coping strategies to manage these issues might be at risk to develop cancer-related anxiety/depression, and therefore may be more at need for support to prevent or decrease such anxiety/depression.…”
Section: Discussionsupporting
confidence: 91%
“…According to the criteria (a neutral point of 3) suggested by Cherrington et al () and unlike previous studies (McCorry et al, ; Shabahang et al, ), we explored other negative aspects of participants' perceptions of this illness: believing that the illness would result in serious consequences, perceiving themselves to have inadequate knowledge of breast cancer, and suffering emotional distress. Participants' perceptions of consequences were found to significantly correlate with avoidance/denial (Hopman & Rijken, ; Richardson et al, ) and poor quality of life (Ashley, Marti, Jones, Velikova, & Wright, ), while psychological distress has been linked to decreased quality of life and compliance with medical therapies (Vetter et al, ). Therefore, measures should be implemented to improve women's emotional status and their understanding of breast cancer.…”
Section: Discussionmentioning
confidence: 99%